2014
DOI: 10.1007/s00404-014-3494-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pneumoperitoneum pressure on surgical field during robotic and laparoscopic surgery: a comparative study

Abstract: Pneumoperitoneum pressure significantly affects the visualization of the abdomino-pelvic cavity in laparoscopic procedures. Otherwise, CO₂ pressure does not affect the visualization of surgical field during robotic surgery. These findings are particularly significant especially at low CO₂ pressure with potential implications on peritoneal environment and the subsequent post-operative patient recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…The use of low intra-abdominal insufflation pressure decreases postoperative pain in laparoscopic cholecystectomy [ 2 , 3 ], and also evidence exists that postoperative pain is decreased when low-pressure pneumoperitoneum (PNP) is used during LDN [ 4 ]. However, the use of low-pressure PNP can impair surgical field visualization [ 5 , 6 ]. To optimize the quality of the surgical conditions, Madsen et al [ 7 ] used a deep neuromuscular block (NMB) to enhance surgical space, measured as the distance from the sacral promontory to the trocar.…”
Section: Introductionmentioning
confidence: 99%
“…The use of low intra-abdominal insufflation pressure decreases postoperative pain in laparoscopic cholecystectomy [ 2 , 3 ], and also evidence exists that postoperative pain is decreased when low-pressure pneumoperitoneum (PNP) is used during LDN [ 4 ]. However, the use of low-pressure PNP can impair surgical field visualization [ 5 , 6 ]. To optimize the quality of the surgical conditions, Madsen et al [ 7 ] used a deep neuromuscular block (NMB) to enhance surgical space, measured as the distance from the sacral promontory to the trocar.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the added value of RAS to both the issue of gas leakage and of pulmonary stress is that CO 2 pressure can be minimized. Whereas pressure for optimal vison at conventional laparoscopy should be at between 10-15 mmHg, robotic vision remains stable and optimal up to 5 mmHg [18].…”
Section: Pro's and Con's Of Rasmentioning
confidence: 99%
“…Viral load might potentially even be higher in operating fields close to the lungs, especially because COVID-19 lesions are mostly seen at the basal and peripheral parts of the lungs [7]. Insufflation pressures should, therefore, be reduced to the lowest level possible without compromising the surgical field exposure; research has demonstrated that robotic vision remains stable and optimal up to 5 mmHg [8]. Care should also be taken to prevent sudden release of trocar valves or non-air-tight change of instruments.…”
mentioning
confidence: 99%